Effects of Nanofertilizers (Mg and Fe) and Planting Data on Productivity and Quality of Potato Tubers in Cold Desert Climate - Khodadadi Karooki, Amir; Yavarzadeh, Mohammadreza; Akbarian, Mohammad Mehdi; Askari, Ali Akbar (Revista Agrogeoambiental, 2021)
Interaction among nanofertilizers supply and planting data may yield synergistic outputs that could influence nutrient use efficiency. To provide insight on this phenomenon, a double split plot based on RCBD with 3 replications were laid out to evaluate the effects spraying solution of nanoparticles magnesium (Mg) and iron (Fe); 0.0 %, 1.0 %, and 2.0 % at flowering and tuber filling stages) and planting data (October 5, 2019 and October 25, 2019) on bioelements, protein nitrogen, and nitrates contents of Sante potato tubers in a cold desert climate (Kerman, Iran). Considering the control group, the use of different dosages of nanofertilizers resulted in a significant increase in the bioelements and pH contents. Besides effects of area and time of planting, their two and three effects on tuber chlorophyll contents were reported significant. The highest protein and nitrogen portion of the potato tubers were related to spraying solution of Mg (1.0 %) + Fe (2.0 %) nanofertilizers. Increasing nanofertilizers supplementation reduced the nitrate content of potato tubers. The results indicated that the application of nanofertilizers significantly increased the carotenoid portion of the potato tubers. The interaction effects of nanofertilizers and planting data on chlorophyll index and calcium levels of potato tubers were completely significant. Our analysis corroborated that application nanofertilizers by spraying during flowering and tuber filling stages enhances potato productivity and quality by improving bioelements or resulting in favorable physiological outcomes and is recommended to farmers.